Análise comparativa da taxa de detecção de câncer de próstata em biópsias guiadas cognitivamente por ressonância multiparamétrica versus guiada por ultrassom transretal - Silva, Juliane Maria Izidio da (2020)
Prostate Cancer (PC) is a solid neoplasm that affects men and represents the second leading cause of cancer death in western countries. Diagnosis is established by biopsy that is usually guided by Transrectal Ultrasound (TRUS), and is indicated if there is a suspicious rectal touch or at elevated PSA (Specific Prostatic Antigen) levels. Studies indicate that Multiparametric Resonance (mpMRI) has better performance in cancer detection, especially aggressive tumors when compared to TRUS. The purpose of this study was to retrospectively compare the PC and csPC (Clinically Significant Prostate Cancer) detection detection rates of cognitively mpMRI guided versus TRUS guided biopsy. We retrospectively evaluated all patients undergoing prostate biopsy at the Prostate Institute of the Oswaldo Cruz German Hospital from May 2011 to April 2019. Group 1 was represented by mpMRI-guided biopsies (n = 501) and Group 2 by those guided by TRUS (n = 688) (control group). In group 1, we correlated the detection rate of PC and csPC according to the degree of suspicion in mpMRI (categorized by v2PIRADS classification). We evaluated the clinical factors and use of mpMRI as predictors of PC and csCP in the general study population. Results: There was no difference in the detection of PC between the two groups. 50.7% (p = 0.866). csPC detection was higher in group 1: 77.8% versus 61.8% OR 2.15, 95% CI (1.51; 3.13) p <0.001, whereas PC detection Gleason score 6 was higher in group 2. mpMRI was an independent predictor of csPC on biopsy OR 1.905 CI 95% (1.351- 2.688) p <0.001. Conclusion: There was no difference in PC detection rate when comparing mpMRI-guided biopsy by the cognitive versus TRUS-guided biopsy. Resonance-guided biopsy was superior with higher detection of csPC and lower diagnosis and Gleason 6 tumors. PIRADS 3, 4 or 5 on mpMRI was an independent predictor of csPC. PIRADS score progression is significantly associated with higher chance of PC and csPC.